A Study of Prevalence of Clindamycin and Erythromycin Resistance of Staphylococcus Aureus in Tishreen University Hospital: Field Study - يازجي, هيثم; زريق, يوسف; الصعبي, منار (Latakia University Journal -Medical Sciences Series, 2021)
Antibiotic resistance is a growing health dilemma and a source of great concern and concern worldwide. Staphylococcus aureus is at the forefront of antibiotic-resistant germs, and is one of the most important pathogens for serious nosocomial infections that result in a high mortality rate, high morbidity rate, and high health care costs related to these infections. From the above, it becomes evident the importance of determining the prevalence of drug resistance of Staphylococcus aureus. In this study, the number of Staphylococcus aureus specimens confirmed by routine diagnostics was 150, 66 female samples (44%) and 84 male samples (56%) that were collected at Tishreen University Hospital in the period between September 2019 - November 2020, and the drug susceptibility test was performed. With the disc diffusion method, the highest rate of resistance to erythromycin was reached (62%), and the lowest drug resistance to linezolid (2.7%). Through this study, it was found that there is no statistically significant relationship between drug resistance to the aforementioned antibiotics and the sex, section, or sample type. And it was also shown through the study that the percentage of strains of Staphylococcus aureus sensitive to oxacillin (MSSA) is higher than that of those strains that are resistant to oxacillin (MRSA), and it was also found through a D-test that reveals the presence of inflammatory resistance to clindamycin (iMLS) that there is a statistically significant relationship between the percentage of this resistance. The MSSA and MRSA strains. The study concluded with the recommendation to monitor the appropriate isolation procedures for Staphylococcus aureus and to strictly scrutinize the techniques of thorough and complete disinfection and sterilization of medical devices, tools and catheters, to provide research facilities, expand research, conduct broader future studies that include the largest number of hospitals and health centers in Syria, and introduce molecular genetic diagnostic technology (such as interaction Polymerase chain reaction (PCR) in future studies to identify the resistant bacterial strains and genes responsible for resistance and a routine D-test that will allow clinicians to choose clindamycin wisely and avoid potential treatment failure.